Study on the effect of the impeller and diffuser blade number on reactor coolant pump performances. Issue 1 (May 2016) - Long, Y; Yin, J L; Wang, D Z; Li, T B
Abstract: In this paper, CFD approach was employed to study how the blade number of impeller and diffuser influences reactor coolant pump performances. The three-dimensional pump internal flow channel was modelled by pro/E software, Reynolds-averaged Naiver-Stokes equations with the k-ε turbulence model were solved by the computational fluid dynamics software CFX. By post-processing on the numerical results, the performance curves of reactor coolant pump were obtained. The results are as follows, with the blade number of the impeller increasing, the head of the pump with different diffuser universally increases in the 8 Q n ∼1.2 Q n conditions, and at different blade number of the diffuser, the head increases with the blade number of the impeller increasing. In 1.0 Q n condition, when the blades number combination of impeller and diffuser chooses 4+16, 7+14 and 6+18, the head curves exist singular points. In 1.2 Q n condition, the head curve still exists singular point in 6+18. With the blade number of the impeller increasing, the efficiency of the pump with different diffuser universally decreases in the 0.8 Q n and 1.0 Q n conditions, but in 1.2 Q n condition, the efficiency of the pump with different diffuser universally increases. In 1.0 Q n condition, the impellers of 4 and 5 blades are better. When the blade number combination of impeller and diffuser choose 4+11, 4+17, 4+18, 5+12, 5+17 and 5+18, the efficiencies relatively have higher values. With the blade number of the impeller increasing, the hydraulic shaft power of the pump with different diffuser universally increases in the 0.8 Q n ∼1.2 Q n conditions, and with the blade number of the diffuser increasing, the power of different impeller overall has small fluctuation, but tends to be uniform. This means the increase of the diffuser blade number has less influence on shaft power.The influence on the head and flow by the matching relationship of the blades number between impeller and diffuser is very complicated, which still need further research.This paper provides a reference for exploring the match relationship between the impeller and diffuser blade number of reactor coolant pump.